Managing scale issues in spatio-temporal movement of tourists modelling - Xia, Jianhong (Cecilia); Arrowsmith, C. (Modelling and Simulation Society of Australia and New Zealand, 2005)
People perceive, think, and behave differently at various spatial and temporal scales. Spatiotemporal modelling of tourist movements considers how people move about or why they exhibit certain movement behaviours. Research into spatio-temporal movements of tourists can be studied from a number of different aspects. Psychologists, for example, are concerned with understanding the cognitive aspects of why people move along particular pathways in preference to alternative pathways. Geographers and tourism researchers are more interested in how people move around particular locations and model what is observed in a visitors’ movement. However in developing simulation models that can be used to emulate tourism movement the issue of scale of movement in both time and space needs to be well understood. It is too simplistic to just apply the same model from one situation to another without thinking about the issues relating to scale. This paper discusses the issues of temporal and spatial scale for the modelling of tourist movements in terms of definition of movement, movement tracking techniques, data acquisition, data analysis, and the transition between the scales using spatio-temporal “zooming theory”.These findings have important implications when developing agent models. The paper first discusses issues relating to measuring, modelling and analysing movement behaviour at two distinct scales, namely the macro and micro level. From this initial discussion the paper then applies techniques discussed to a specific study location at Phillip Island in Victoria. The first scale examined is the macro level which covers the whole of Phillip Island. At the micro scale tourist movement behaviour is examined for a specific geographic location, the Koala Conservation Centre. Modelling the spatio-temporal movement of tourists at the macro level aims to represent the general travel patterns of a variety of tourist types. However movements of tourists modelled at the micro level relies on real-time and detailed tracking of tourists in a confined geographic area. Location-based service provision, security, emergency management and tourist wayfinding decision making are dependent on micro-scale movements of tourists. This paper not only represents the differences of tourist movement tracking and modelling methods between these two scales but also explains the transition of tourist movement between two scales using spatio-temporal zooming theory.